Emotional bias and waking salivary cortisol in relatives of patients with major depression - Le Masurier, M; Cowen, P; Harmer, C (2007)
Background: Biases in the processing of emotional information have been shown to be abnormal in subjects with major depression, both during an episode and after full recovery. However, it is unclear whether these biases are a cause or an effect of the depression. This study set out to explore whether such biases represent a vulnerability factor for depression by looking at unaffected first-degree relatives of those with major depressive disorder. We also measured waking salivary cortisol, as the regulation of the hypothalamo-pituitary-adrenal (HPA) axis is thought to be impaired in depressive disorder. Method: Twenty-five female relatives and 21 age-matched controls completed a facial expression recognition task, an emotional categorization task with positive and negative personality characteristics, and had their waking salivary cortisol measured on a work day and a non-work day. Results: The depressed relative group was significantly faster to recognize facial expressions of fear than controls. The depressed relative group also showed significantly increased reaction time to recognize positive versus negative personality characteristics in the categorization task. There was no difference in waking salivary cortisol between groups, although there was an effect of work day versus non-work day. Conclusions: Subtle biases in the processing of emotional information may exist in the unaffected first-degree relatives of those with depression. As such, this may represent a familial vulnerability factor to developing a depressive illness. © 2006 Cambridge University Press.